Distance Matters, Except When It Doesn't: Discontinuities in Virtual Work - Mary Beth Watson-Manheim; Chudoba, Katherine M.; Kevin Crowston (Academy of Management Conference, 2007)
Virtual work has become an increasingly common phenomenon in today's organizations. Substantial and continuing changes in organizational processes and IT infrastructure have increased the pace and intensity of working across traditionally impermeable boundaries, enabling diverse forms of collaboration. However, our understanding of the consequences and implications of virtual work still lags and research results have been contradictory. We suggest that some of these inconsistencies have been because the boundaries that characterize virtual work-time, space, culture, organization, and so forth-are objective demarcations that are not uniformly problematic. It is only when those working in virtual settings perceive a boundary to be a discontinuity that it hinders work processes. We develop a model of virtual work that differentiates between boundaries and discontinuities, which helps account for contradictory findings. By examining the process of virtual work in more detail, we can uncover issues that are the underlying cause of problems, rather than deal with the more obvious symptoms that can mask underlying problem. Our model has implications both for research and for those working in virtual environments.
Keywords: Discontinuity; Virtuality